OPTIMISATION AND MODELING OF FLUORIDE REMOVAL BY ELECTROCOAGULATION IN A CONTINUOUS FLOW BIPOLAR REACTOR - Benderrah, T; Djedid, M; Naceur, M.W; Benalia, M (university of el oued/جامعة الوادي, 2021)
In this study an experimental design was employed to investigate the effects of different operating conditions on the removal of fluoride by electrocoagulation with aluminum electrodes. Box-Behnken design was then used for optimizing and modeling the electrocoagulation process and for evaluating the effects and interactions of variables: current density (i, A/m2), flow rate (Q, mL/min), and initial fluoride concentration (C0, mg/L). The proposed model fitted very well with the experimental data. R2 adjusted correlation coefficients (AdjR2: 0.98) for fluoride removal efficiency showed a high significance of the model. The model predicted for a maximum removal of fluoride (95.07%) at the optimum operating conditions (120 A/m2, 120 mL/min and 30 mg/L) after the EC process was 94.76% at the same optimum operating conditions
Article
Keywords: Electrocoagulation; Fluoride removal; Modeling; Optimization; continues flow